Mosquito vector diversity and abundance in southern Botswana, in a global context of emerging pathogen transmission - Ntebaleng Makate; Pleasure Ramatlho; Tefo Kesaobaka Kgoroebutswe; Katherine Laycock; Giacomo Maria Paganotti (Journal of Public Health in Africa, 2022)
Background. The continued spread of infectious diseases by mosquitoes remains a formidable obstacle to the well-being of the people all over the world. Arboviruses are spread from one vertebrate host to another by vectors through intricate transmission cycles that involve the virus, the vertebrate host, and the vector. It is essential to acquire a better understanding of the current abundance and distribution of major vectors in order to adequately prepare for the possibility of arbovirus outbreaks. This is because the abundance and distribution of these major vectors determines the human populations that are at risk for the diseases that they transmit. The effects of climate change on the amount of mosquitoes and their ability to survive the seasons have had a substantial impact on the spread of diseases that are transmitted by vectors in many different parts of Botswana.